Psychoactive substance abuse among commercial bus drivers in Umuahia, Abia State, South-Eastern Nigeria: an uncontrolled "epidemic" with attendant road traffic crashes - Roseline Oluyemisi Akande; Joel Olufunminiyi Akande; Olaniyan Akintunde Babatunde; Adeola Olajumoke Ajayi; Akindele Amos Ajayi; Roseline Olabisi Ige; Ajedotun Shittu Saliu; Abayomi Akande; Muideen Babatunde Olatunji (BMC, 2023)
Abstract Background information The unprecedented depletion of the productive workforce has been majorly attributed to road traffic crashes (RTCs). The attendant consequences of this depletion have been found to constitute a serious global public health challenge, with the use of psychoactive substances among drivers implicated in every three of five motor vehicle accidents. Hence, this study assessed the pattern and explored the determinants of substance abuse among commercial bus drivers in Umuahia, Abia State. Methods A descriptive cross-sectional design was used for the study. Four hundred commercial bus drivers were recruited from selected motor parks in Abia-state, using a multistage sampling technique from October to December 2020. A pretested, interviewer-administered questionnaire was administered to obtain socio-demographics and information on substance abuse. Data were analyzed using IBM SPSS version 25; bivariate analysis was done using Chi-square. The level of significance was at 5%. Results The mean age of the respondents was 40.03 ± 10.50 years. The proportion of respondents who had ever abused a psychoactive substance was 74.6%. The most commonly abused substances among drivers include alcohol (51%), cigarettes (27%), and alcoholic herbal mixtures (16%). The study participants had poor knowledge (54.5%) and poor perception (63.2%) about psychoactive substance abuse. Among the factors found to be significantly associated with substance abuse among respondents were ethnicity (p = 0.002), religion (p = 0.009) and monthly income (p = 0.013) of the respondents, poor knowledge (p < 0.001) and poor perception (p < 0.001). However, this study found religion (p = 0.031; OR = 5.469; CI = 1.170 to 25.555), knowledge (p < 0.001; OR = 4.21; CI = 2.201 to 8.287) and perception (p < 0.001; OR = 9.828; CI = 15.572 to 65.052) as factors that were associated with the higher likelihood of psychoactive substance abuse. Conclusion Religion, poor knowledge and perception were associated with the higher likelihood of psychoactive substance abuse among commercial bus drivers. Targeting commercial bus drivers for educational interventions and using religious leaders as conveyor belts may reduce the use of psychoactive substances among them.